2000
DOI: 10.1212/wnl.55.11.1626
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal and cortical atrophy predict dementia in subcortical ischemic vascular disease

Abstract: Background-The cause of dementia in subcortical ischemic vascular disease (SIVD) is controversial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
284
5
4

Year Published

2003
2003
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(322 citation statements)
references
References 51 publications
(74 reference statements)
29
284
5
4
Order By: Relevance
“…The pattern of cognitive impairment is consistent with models of impaired cortical and subcortical neuronal pathways (Kramer et al, 2002). Complex interactions in producing cognitive decline have been shown (Fein et al, 2000) and changes in cortex and hippocampus, while other interactions suggested significant correlations between cortical lesions and frontal atrophy (Burton et al, 2003;Hentschel et al, 2003). Preclinical (Kimura et al, 2000) and clinical evidence (Swartz and Black, 2002) indicate that a cholinergic deficit similar to that seen in Alzheimer's dementia (AD) may be associated with vascular dementia (VaD); which suggests that these patients may benefit from treatment with cholinesterase inhibitors, as has been confirmed in recent studies (Erkinjuntti et al, 2000).…”
Section: Introductionsupporting
confidence: 67%
“…The pattern of cognitive impairment is consistent with models of impaired cortical and subcortical neuronal pathways (Kramer et al, 2002). Complex interactions in producing cognitive decline have been shown (Fein et al, 2000) and changes in cortex and hippocampus, while other interactions suggested significant correlations between cortical lesions and frontal atrophy (Burton et al, 2003;Hentschel et al, 2003). Preclinical (Kimura et al, 2000) and clinical evidence (Swartz and Black, 2002) indicate that a cholinergic deficit similar to that seen in Alzheimer's dementia (AD) may be associated with vascular dementia (VaD); which suggests that these patients may benefit from treatment with cholinesterase inhibitors, as has been confirmed in recent studies (Erkinjuntti et al, 2000).…”
Section: Introductionsupporting
confidence: 67%
“…Cortical gray matter volume reflects the degree of cortical atrophy, with smaller cortical gray matter volume indicating greater cortical atrophy. In AD, cortical gray matter correlates significantly with overall cognitive functioning and degree of dementia, and thus can be viewed as a marker of dementia severity (Fein et al, 2000;Mungas et al, 2001). When cortical gray matter, hippocampal volumes and white matter signal hyperintensities were simultaneously entered into a regression model predicting immediate recall, only cortical gray matter volume explained a significant proportion of the variance.…”
Section: Discussionmentioning
confidence: 99%
“…Image acquisition and segmentation methods have been previously described (Fein et al, 2000;Mungas et al, 2001). A computer algorithm was used to classify brain MRI pixels first into principal tissue types of gray matter, white matter, and cerebrospinal fluid.…”
Section: Methodsmentioning
confidence: 99%
“…Segmentation to obtain quantitative volumes of lacunes (LAC), WMH, cortical gray matter (CGM), and hippocampal volume (HV) was accomplished using the T-1 and T-2 weighted axial images. Image segmentation methods have been previously described elsewhere (Fein et al, 2000). A computer algorithm was used to classify brain MRI pixels first into principle tissue types of gray matter, white matter, and cerebrospinal fluid.…”
Section: Mri Methodsmentioning
confidence: 99%